2018
DOI: 10.1080/10245332.2018.1540518
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment and risk factors of liver fibrosis in patients with thalassemia major using shear wave elastography

Abstract: Objectives: This study aimed to estimate the prevalence of liver fibrosis and assess the risk factors for developing significant liver fibrosis in patients with Thalassemia Major (TM). Methods: All patients with TM over the age of 10 years were included in the study. Results: A total of 94 eligible patients underwent 2-D SWE. The median age was 26.7 years. The median of the average 5-year serum ferritin (5yrSF) and liver iron concentration (LIC) assessed by MRI T2* were 1326 µg/L and 6.7 mg/g dw, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
1
20
0
2
Order By: Relevance
“…SWS overcomes the limitations of strain elastography by automatically generating an acoustic force that creates a mechanical impulse, leading to tissue displacement in the form of shear‐waves. This technology has been widely used in the assessment of breast or prostate mass and liver cirrhosis 17‐19 . The advantage of SWS is that the generation of the mechanical impulse is operator‐independent 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWS overcomes the limitations of strain elastography by automatically generating an acoustic force that creates a mechanical impulse, leading to tissue displacement in the form of shear‐waves. This technology has been widely used in the assessment of breast or prostate mass and liver cirrhosis 17‐19 . The advantage of SWS is that the generation of the mechanical impulse is operator‐independent 20 …”
Section: Introductionmentioning
confidence: 99%
“…This technology has been widely used in the assessment of breast or prostate mass and liver cirrhosis. [17][18][19] The advantage of SWS is that the generation of the mechanical impulse is operator-independent. 20 The cervical canal is surrounded by a layer of longitudinal smooth muscle fibers that are wrapped circumferentially by a layer of smooth muscle and collagenous cells, which may act as a "sphincter" to maintain the pregnancy.…”
mentioning
confidence: 99%
“…Previous studies have shown that ARFI-e is a reliable method in addition to the T-e in the evaluation of liver fibrosis and cirrhosis. 26 Al-Khabori et al 27 suggested that male sex as an independent factor increases the risk of liver fibrosis in patients with β-TM. In the present study, it was found that the liver ARFI-e measurements of boys were significantly higher than those of girls (p = .023), and this result supports their suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…57 Liver disease is also associated with an increase in inflammatory cytokines, which negatively affect the hypothalamus pituitary-thyroid axis, leading to suppressed TSH levels in some patients. 58 In the light of eradication of HCV in the thalassemia population with direct-acting antiviral drugs, the prevalence of thyroid dysfunctions could be ameliorated. However long-term studies are needed to confirm this assumption.…”
Section: Clinical Manifestations and Other Diagnosticmentioning
confidence: 99%